(untitled) (Communications in Computational Physics, 2009)
Aerosol modelling is very important to study and simulate the behavior of aerosol dynamics in atmospheric environment. In this paper, we consider the general nonlinear aerosol dynamic equations which describe the evolution of the aerosol distribution. Continuous time and discrete time wavelet Galerkin methods are proposed for solving this problem. By using the Schauder's fixed point theorem and the variational technique, the global existence and uniqueness of solution of continuous time wavelet numerical methods are established for the nonlinear aerosol dynamics with sufficiently smooth initial conditions. Optimal error estimates are obtained for both continuous and discrete time wavelet Galerkin schemes. Numerical examples are given to show the efficiency of the wavelet technique